Effect of transition metal (Cu and Pt) doping/ co-doping on hydrogen gas sensing capability of graphene: A DFT study. (26th April 2021) - Singla, Mehak; Sharma, Deepa; Jaggi, Neena
Abstract: Carbon nano-materials are found to demonstrate good hydrogen gas sensing capability and researchers are trying their modified derivatives for enhanced sensitivity. Studies have confirmed improvement in sensing performance of graphene when doped with N or Si or Sb. However, effect of the doping of graphene with transition metals of comparable size on its hydrogen sensing properties has not yet been studied. In the present study, we investigated the sensitivity of pristine graphene, Pt-doped graphene; Cu-doped graphene and Pt–Cu co-doped graphene surface towards hydrogen molecule adsorption utilizing density functional theory (DFT) by ab initio method. The adsorption energies for the optimized geometries have been calculated to probe the suitability and effectiveness of the modified graphene structures for Hydrogen sensing. In addition, the electronic properties for instance charge transfer analysis, band gap and density of states have also been taken into consideration. The reactivity of graphene surface for hydrogen adsorption was found to be greatly enhanced with Pt–Cu co-doped graphene surface as demonstrated by the adsorption energies and electronic properties. Highlights: Modified structural and electrical properties of doped/co-doped graphene. Improved hydrogen sensing ability of graphene co-doped with Cu and Pt. In the co-doped system, more than four times increase in adsorption energy. Effective analysis to customize graphene based H2 gas sensor.